Mechanocatalysis with electrically induced contractile electro-active polymer - Nur, Hadi; Ramli, Zainab; Hoo, Amelia Boon; Lim, Kheng Wei (Faculty of Science, 2009)
One of the largest challenges in heterogeneous catalysis is how to control the adsorption and desorption catalytic cycle on the surface of catalyst. Therefore, the ultimate goal of this study is to design a new heterogeneous catalytic system based on an idea that the surface charge of the solid catalyst can be controlled by applying electric field in order to improve the efficiency of adsorption and desorption in catalytic cycle processes. Electric-field-induced oxidation of benzhydrol to benzophenone over electrically conducting surface containing titanium dioxide has been carried out by using hydrogen peroxide as oxidant. Polypyrrole and titanium dioxide have been used as electrically conducting materials and catalytic active site, respectively. The results suggest the occurrence of the synergistic effect of the electric field and titanium dioxide. The electric field on the generation of surface charge to induce the adsorption of organic substrate has been confirmed by methylene blue adsorption experiments. The study is also extended to photocatalysis in which the removal of methylene blue under the irradiation of UV light and electric field is chosen as a model catalytic system. One expects that the electric field will induce the degradation of metylene blue over polypyrrole containing titanium dioxide. There is no significant effect of the irradiation of UV light was observed in this process although the removal of methylene blue increased under electric field. As a global guide for future actions, this work opens new perspectives for the use of electrically conducting surface containing titanium dioxide in electric-field-induced liquid phase oxidation catalysis.